ANALISIS KUALITATIF KANDUNGAN FORMALIN PADA TAHU YANG DIJUAL DIBEBERAPA PASAR DI KOTA PALU - Rismawaty Sikanna (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
It had been an investigation on qualitative analysis of formalin in tofu that sold in Palu markets, purpose of this study was to identifity content of formalin in samples of tofu.This identification can know with changes of the colour of the filtrate in samples of tofu from pink to be brown until the colour fed off in 30 minutes. Samples of tofu were taken from some traditional and modern markets in Palu city. The results obtained 66.7% of all of tofu samples identified content of formalin there were 6 samples with sign of M-3, T-2, T-6, T-5, M-2, and T-4, but 3 samples with sign of T-3, M-1 and T-1 not found. It was supported of texture of tofu samples. There showed that producen of tofu in Palu city is still using formalin as preservative substance in process of tofu production.Keywords: Qualitative analysis of formalin, tofu.